2010
DOI: 10.1182/blood.v116.21.516.516
|View full text |Cite
|
Sign up to set email alerts
|

The Pan-Bcl-2 Family Inhibitor 97C1 Targets Blast Crisis Chronic Myeloid Leukemia Stem Cells but Spares Normal Cord Blood Progenitor Cells

Abstract: 516 Introduction: Several studies have demonstrated the role of leukemia stem cells (LSC) in the development and maintenance of human chronic myeloid leukemia (CML). These cells, which first develop in chronic phase CML (CP CML) with acquisition of the BCR-ABL fusion protein, are often quiescent and can be highly resistant to apoptosis induced by drugs and radiotherapy that target rapidly dividing cells. Data has also shown that CML LSC become increasingly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These results open the possibility of targeting JAK2 in CML either through a specific JAK2 TKI, or the PP2A activator FTY720. Another study presented at ASH tested the activity of a novel high potency pan‐Bcl‐2 inhibitor, 97C1, and demonstrated that this drug could effectively kill stem cells from blast crisis CML in vitro and in vivo [28], possibly through combined inhibition of Bcl2, BclX, and Mcl1.…”
Section: Some Topical Preclinical and Basic Science Issues In CMLmentioning
confidence: 99%
“…These results open the possibility of targeting JAK2 in CML either through a specific JAK2 TKI, or the PP2A activator FTY720. Another study presented at ASH tested the activity of a novel high potency pan‐Bcl‐2 inhibitor, 97C1, and demonstrated that this drug could effectively kill stem cells from blast crisis CML in vitro and in vivo [28], possibly through combined inhibition of Bcl2, BclX, and Mcl1.…”
Section: Some Topical Preclinical and Basic Science Issues In CMLmentioning
confidence: 99%